Digital resources and the production of historical knowledge based on material evidence: reflections on database production for researches in Classical Archaeology - Dias, Carolina Kesser Barcellos; Souza, Camila Diogo de; Cerqueira, Fábio Vergara (Romanitas - Revista de Estudos Grecolatinos, 2018)
Over the last few decades, major advances in historical knowledge about Classical Antiquity have occurred due to archaeological studies with regard to new approaches, which reallocate the relationship between written and material sources in the interpretation of the past. The description and the typological classification based on morphological, chronological, stylistic and technical aspects of the material culture are two major methodological resources for the production of archaeological knowledge. Current electronic innovations brought numerous contributions to researchers by means of inter-related data analysis programs that create the possibilities for data access and knowledge dissemination. These programs also enable future perspectives and new interpretations of the same object of study. Thus, the production of databases plays a key role in producing catalogs, and promotes a greater variability of interpretations. However, it is necessary to reflect on the goals, purposes and the scope of such methodological resources for the academic community and for scientific research as a whole, as well as issues related to public access to information. In this article, we bring up the discussion of subjects presenting some specific examples of archaeological corpora systematization and database production in the field of Classical Archaeology research. These examples and models constitute new approaches and perspectives of data analysis, which have been developed by the Laboratório de Estudos sobre a Cerâmica Antiga (LECA) da Universidade Federal de Pelotas (UFPel).
Keywords: Archaeology; Material culture; Ceramics; Digital resources; Database